Effects of geometric parameters on the performance of solar chimney power plants. (1st November 2018) - Toghraie, Davood; Karami, Amir; Afrand, Masoud; Karimipour, Arash
Abstract: In this study, the influences of geometrical properties on a solar chimney were investigated numerically by applying the κ − ε turbulence model, continuity, momentum, and energy equations in the 3D finite volume approach inside a solar chimney power plant. The following variables should be involved: collector radius (Rcl ), collector height (Hcl ), chimney height (Hch ), chimney radius (Rch ), and heat flux ( q ″ ). The effects of changes in these variables on temperature, velocity, pressure distributions, efficiency, and output power were investigated. The results indicated that output power and solar chimney efficiency have positive relationships with chimney height and collector radius but a negative one with collector height. In addition, it was found that the parameter of chimney radius has an optimum range which has the maximum values for efficiency and output power. Highlights: Investigating the influences of geometrical properties on a solar chimney performance. Using the κ − ε turbulence model and the 3D finite volume approach. Presenting variables effects on temperature, velocity, pressure, efficiency, and output power. Power and efficiency have positive relationships with chimney height and collector radius. Chimney radius has an optimum range for obtaining maximum efficiency and output power.